Impact of clinical factors and personality on the decision to have a second child. Longitudinal cohort‐study of first‐time mothers. (18th December 2013) - Klint Carlander, Anna‐Karin; Andolf, Ellika; Edman, Gunnar; Wiklund, Ingela
Abstract Objective To investigate which factors related to the first birth influence subsequent reproduction within 5 years after the birth. Design Prospective cohort study. Setting University hospital, Stockholm, Sweden. Sample Cohort of 547 first‐time singleton mothers with a normal pregnancy recruited prospectively of whom 451 women consented to follow‐up 5 years later. Methods Data were collected by several questionnaires on sexual, reproductive and childbirth‐related factors as well as on personality, postnatal depression, fear of childbirth and contact between mother/child. Medical records were also used. Associations between these factors and having a second child were analyzed using logistic regression. Main outcome measures Women's subsequent reproduction. Results Planning a second child at 9 months postpartum was most important in determining to have a second child. Women who had restored their sex life 9 months after birth and women who had a high score in the personality monotony avoidance scale, were less likely to give birth to a second child. No differences were observed regarding mode of delivery, factors related to birth and having a second child, nor was there an association between postnatal depression, fear of childbirth, a negative birth experience and self‐estimated contact with the child and subsequent reproduction. Conclusions Circumstances in relation to the first birth, such as mode of delivery and a negative birth experience, did not affect subsequent reproduction. Planning another child by 9 months after birth was the strongest factor correlated with having a second child.